Palladium‐Catalyzed Defluorinative Alkylation of gem‐Difluorocyclopropanes: Switching Regioselectivity via Simple Hydrazones - Lv, Leiyang; Li, Chao‐Jun (Angewandte Chemie International Edition, 2021)
Conventional approaches for Pd‐catalyzed ring‐opening cross‐couplings of gem‐difluorocyclopropanes with nucleophiles predominantly deliver the β‐fluoroalkene scaffolds (linear selectivity). Herein, we report a cooperative strategy that can completely switch the reaction selectivity to give the alkylated α‐fluoroalkene skeletons (branched selectivity). The unique reactivity of hydrazones that enables analogous inner‐sphere 3,3′‐reductive elimination driven by denitrogenation, as well as the assistance of steric‐embedded N‐heterocyclic carbene ligand, are the key to switch the regioselectivity. A wide range of hydrazones derived from naturally abundant aryl and alkyl aldehydes are well applicable, and various gem‐difluorocyclopropanes, including modified pharmaceutical and biological molecules, can be efficiently functionalized with high value alkylated α‐fluorinated alkene motifs under mild conditions. A highly effective Pd‐catalyzed defluorinative alkylation of gem‐difluorocyclopropane with branched selectivity was achieved by using a cooperative strategy that integrated the unique trifunctional character of hydrazones with Pd/NHC catalysis.